Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

“Great writing always sings”: Dorothy Allison Speaks - Grué, Mélanie; Allison, Dorothy (The Southern Quarterly, 2016)
Brought up in a Southern poor white family and the victim of her stepfather's abuse from a very early age, Allison turned to writing to address difficult issues which few writers dare to deal with: child abuse, class-based discrimination, transgressive lesbianism, and overall violence. [...]I started burning them, or destroying them. Because they were just too dangerous to be in the world. Some of it is not so bad: bluegrass and rhythm 'n' blues, some of the gospel music I love, it stays with me.
Keywords: amériques; approches et analyses; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; écriture des femmes*; états-unis

The color of violence: The incite! anthology - INCITE! Women of Color Against Violence (Duke University Press, 2016)
The editors and contributors to Color of Violence ask: What would it take to end violence against women of color? Presenting the fierce and vital writing of organizers, lawyers, scholars, poets, and policy makers, Color of Violence radically repositions the antiviolence movement by putting women of color at its center. The contributors shift the focus from domestic violence and sexual assault and map innovative strategies of movement building and resistance used by women of color around the world. The volume's thirty pieces—which include poems, short essays, position papers, letters, and personal reflections—cover violence against women of color in its myriad forms, manifestations, and settings, while identifying the links between gender, militarism, reproductive and economic violence, prisons and policing, colonialism, and war. At a time of heightened state surveillance and repression of people of color, Color of Violence is an essential intervention.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; droits des femmes*; femmes* autochtones; femmes* de couleur; femmes* immigrantes; hétérosexisme; intersectionnalité; justice reproductive; justice sociale; militance; outils; ouvrages de références; périodes historiques; racisme; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

La couleur pourpre - Walker, Alice (Pavillons poche, 1772-5313, 2016)
Dans la grande tradition du roman sudiste, La Couleur pourpre, qui dénonce l'oppression raciale et sexuelle dont furent victimes les femmes noires, a fait date. Celie et Nettie sont deux soeurs séparées à l'adolescence mais liées par un amour indéfectible que ne terniront ni les brimades ni le mépris, ni les guerres ni l'absence. Celie, mariée enfant à un homme violent, ne reçoit pas les lettres que lui adresse Nettie, devenue missionnaire en Afrique, car son mari les subtilise. Ignorant l'adresse de sa soeur, elle-même envoie ses lettres au Bon Dieu. Une correspondance sans espoir de réponse. Une correspondance qui sauvera les deux femmes du désespoir. Lauréat du prix Pulitzer et de l'American Book Award en 1983, La Couleur pourpre a été adapté au cinéma en 1984 par Steven Spielberg
Keywords: 1900-1999; amériques; approches et analyses; esclavagisme; histoire et politique; périodes historiques; racisme; roman; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; violences conjugales; violences contre les femmes*; violences raciales; états-unis